Розробка комп'ютерної гри «Forgotten Island: Hero Artifacт» - Скороход, М. М. (ХНУРЕ, 2025)
This work is devoted to the analysis of the game genre "roguelike", available analogues in the gaming industry and the creation of a game using the Unreal Engine 5 engine. This work explores the "roguelike" game genre, its defining mechanics, and its influence on the gaming industry. It analyzes key features such as procedural generation, permadeath, and turn-based gameplay while comparing notable industry analogues, including roguelite variations. The study also focuses on the practical development of a roguelike game using Unreal Engine 5.
Keywords: комп'ютерна гра; розробка ігор